2016
DOI: 10.3390/rs8010069
|View full text |Cite
|
Sign up to set email alerts
|

Global Gap-Free MERIS LAI Time Series (2002–2012)

Abstract: This article describes the principles used to generate global gap-free Leaf Area Index (LAI) time series from 2002-2012, based on MERIS (MEdium Resolution Imaging Spectrometer) full-resolution Level1B data. It is produced as a series of 10-day composites in geographic projection at 300-m spatial resolution. The processing chain comprises geometric correction, radiometric correction, pixel identification, LAI calculation with the BEAM (Basic ERS & Envisat (A)ATSR and MERIS Toolbox) MERIS vegetation processor, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 62 publications
(52 reference statements)
0
17
0
1
Order By: Relevance
“…MERIS LAI product, acquired from https://centaurus.caf.dlr.de:8443/, is generated every 10 days in 1/360°spatial resolution (Tum et al, 2016). The algorithm is based on the training of a neural network over a database of simulated top-of-atmosphere radiances, using a coupled leaf-canopy-atmosphere radiative transfer model (Bacour, Baret, B eal, Weiss, & Pavageau, 2006).…”
Section: Meris Lai Productmentioning
confidence: 99%
See 1 more Smart Citation
“…MERIS LAI product, acquired from https://centaurus.caf.dlr.de:8443/, is generated every 10 days in 1/360°spatial resolution (Tum et al, 2016). The algorithm is based on the training of a neural network over a database of simulated top-of-atmosphere radiances, using a coupled leaf-canopy-atmosphere radiative transfer model (Bacour, Baret, B eal, Weiss, & Pavageau, 2006).…”
Section: Meris Lai Productmentioning
confidence: 99%
“…Aiming at this goal, we examined their trends, interannual variabilities, and uncertainty variations. We also compared the four long-term LAI products with other widely used but short-term products: GEOV1 ; MERIS (Tum et al, 2016); MODIS Collection 5 (C5) (Shabanov et al, 2005); and MODIS Collection 6 (C6) (Yan et al, 2016). Consequently, three time periods were investigated separately: 30-year long-term period (1982( ), pre-MODIS period (1982( -1999, and overlap period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) (Pedelty et al, 2007), and 1 km resolution Terra/MODIS surface reflectance datasets (MOD09) since 2001 (Xiao et al, 2016).…”
mentioning
confidence: 99%
“…For example, short gaps in TWS records could hinder the analysis and interpretation of temporal variability by introducing errors in the extracted amplitude and phase of the annual cycle, non-seasonal residual signals, as well as in secular trends and associated significance levels [39][40][41] and could also increase the level of uncertainty in the spectral modeling of temporal variability and cyclicity [42]. Long gaps, on the other hand, could obscure the temporal patterns of TWS data and consequently distort the results of any statistical analysis [38,43].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of reviewed studies (61) facilitated more than one validation method. Hereby, a variety of studies showed, in particular, the combination of an intercomparison of products with a comparison to reference data [9,21,35,48,53,54,57,59,84,97,[120][121][122][123][124]129,133,135,139,[141][142][143][144][145]. This dual approach can provide an indication of general remote sensing performance for a particular research area or, on the other hand, illustrate improvements of novel methods in relation to existing products [35,71,136].…”
Section: Combination Of Methodsmentioning
confidence: 97%